The financial situation of families and the quality of life and coping with stress of children with ASD during the SARS-CoV-2 pandemic - Anna Gagat-Matula (Risks, 2021)
The aim of the study was to compare children with ASD from families with low and medium financial status in terms of quality of life and coping with stress during the SARS-CoV-2 pandemic and the material status of the family related to their financial situation during the pandemic. The diagnostic survey method was used in the research study. A total of 120 children with autism spectrum disorder (ASD) aged 11-14 years participated in the study. The following tools were used to achieve the goal: Quality of Life of Students by S. Kowalik, "Jak Sobie Radzisz" by Z. Juczy ' nski and N. Ogi' nska-Bulik and a proprietary questionnaire by the author. The research results indicate that during the SARS-CoV-2 pandemic, children with ASD from families with an average financial status are more satisfied with functioning in the family and more satisfied with themselves than children from families with a low financial status. Moreover, children with ASD from low-status families prefer strategies of focusing on emotions, which are not constructive and make functioning difficult, more often than their peers from families with average financial status. The results of the research show a positive correlation between the quality of life in the dimensions of satisfaction with the family, one's local environment and oneself and active coping (disposition) and seeking social support; and a negative correlation with the strategy of focusing on emotions (disposition). It is advised that families with children with ASD be supported during the pandemic.
Keywords: 330; material situation; quality of life; coping with stress; spectrum of autistic disorders